The relationship between capital structure and performance of non-financial firms listed in Amman Stock Exchange - Alfawareh, Faraj Salman Hameed (2019)
The main objective of the current study is to examine the relationship between capital structure and firm’s performance particularly focusing on the Jordanian firms listed on Amman Stock Exchange. The current study uses 95 sample firms from non-financial firms listed on Amman Stock Exchange. The period of study is 5 years (2013-2017). The series of regressions have been shown and the results are reported based on fixed effect model. The findings show that all variables represent capital structure by Long Term Debt to Total Assets, Total Debt to Total Assets, Size, Sales Growth, Tangibility, and Liquidity have the relationship with firm’s performance represent by ROA and Tobin’s Q. Total Debt to Total Assets and growth have a positive significant relationship with firm’s performance. Meanwhile, The Long-Term Debt to Total Assets and Liquidity show insignificant relationship with firm’s performance. Similarly, Tangibility has a significant negative relationship with ROA and Tobin’s Q.